PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY PADA MATERI TEORI KINETIK GAS SMA KELAS XI - Rifqa Gusmida; M. Rahmad '; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to design and build a educational media of learning physics are valid uses Augmented Reality technology in the kinetic theory of gases for senior high school grade XI. This research was research and Development (R & D) using instructional design type ADDIE includes the step of analysis, design, development, implementation and evaluating. Sources of data in this study is the assessment of data provided by the validity of the 6 validator, consisting of three lecturers and three teachers. Aspects assessed include designing, pedagogic, learning content and ease of use. Data analysis technique used is descriptive analysis techniques using descriptive statistics. The final result of media validation assessment of all aspects of learning physics had validity value of 3.55 with a very high category. Based on these results, we can conclude that the media of learning physics using Augmented Reality technology in the kinetic theory of gases for a high school grade XI declared valid categorized as very high, so that used in the process of learning and teaching.Keywords: Education Media, Augmented Reality, Kinetic Theory of Gases, Validation